1981
DOI: 10.1139/v81-263
|View full text |Cite
|
Sign up to set email alerts
|

Charge exchange mass spectra of some C5H10 isomers

Abstract: Reagent gas systems are described for use in a single-source chemical ionization mass spectrometer which permit charge exchange mass spectra to be obtained using CS2+•(∼10.2 eV), COS+•(11.2 eV), Xe+•(∼12.5 eV), CO+•(14.0 eV), N2+•(15.3 eV), and Ar+• (15.8 eV) (recombination energies in brackets) as the major reactant ions. Using these reagent gas systems the charge exchange mass spectra of cyclopentane, 1-pentene, 3-methyl-l-butene, 2-methyl-l-butene, 2-pentene, and 2-methyl-2-butene have been obtained. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Use of differences in fragmentation patterns after collision-induced dissociation (CID) is still the most common and well-studied approach. 1À3,5À7,9,10 Other techniques exploit differences in physical properties of isomeric ions: migration rates of ions through a neutral gas (ion mobility spectrometry), 11,12 reactivities of ions, 13,14 charge exchange MS, 15,16 direct photon absorption or emission, 17,18 variable wavelength photodissociation in the infrared, 19À23 visible 24 or ultraviolet 25 with one or more 26,27 lasers, differences in photodissociation by rapid pulse shaping over an approximate Gaussian wavelength distribution centered at 800 nm, 28,29 and relatively high-resolution spectroscopy…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Use of differences in fragmentation patterns after collision-induced dissociation (CID) is still the most common and well-studied approach. 1À3,5À7,9,10 Other techniques exploit differences in physical properties of isomeric ions: migration rates of ions through a neutral gas (ion mobility spectrometry), 11,12 reactivities of ions, 13,14 charge exchange MS, 15,16 direct photon absorption or emission, 17,18 variable wavelength photodissociation in the infrared, 19À23 visible 24 or ultraviolet 25 with one or more 26,27 lasers, differences in photodissociation by rapid pulse shaping over an approximate Gaussian wavelength distribution centered at 800 nm, 28,29 and relatively high-resolution spectroscopy…”
mentioning
confidence: 99%
“…The problem has been approached in different ways, some more successful than others, depending on the nature of the precursor ions. Use of differences in fragmentation patterns after collision-induced dissociation (CID) is still the most common and well-studied approach. , ,, Other techniques exploit differences in physical properties of isomeric ions: migration rates of ions through a neutral gas (ion mobility spectrometry), , reactivities of ions, , charge exchange MS, , direct photon absorption or emission, , variable wavelength photodissociation in the infrared, visible or ultraviolet with one or more , lasers, differences in photodissociation by rapid pulse shaping over an approximate Gaussian wavelength distribution centered at 800 nm, , and relatively high-resolution spectroscopy in cold traps. , In cases relying on dissociation of a precursor ion, the mass spectra may be too similar to assign particular isomers from the product ion ratios with confidence. This can occur for several reasons: (1) product ion ratios frequently differ somewhat among different instruments; (2) product ion ratios can vary somewhat using the same instrument under supposedly identical conditions; (3) methods of processing digitized spectral data vary, and at least some error is introduced in quantitation of spectral peaks depending on the processing method; (4) white noise is present to varying extents; and (5) a proper statistical evaluation of data is often not performed.…”
mentioning
confidence: 99%
“…reactant ion (R+-). Charge exchange offers a simple method for varying the amount of internal energy initially deposited in "1"' (8). Thus, the fragmentation behavior of M+i can be controlled by varying the exothermicity of eq 1.…”
mentioning
confidence: 99%
“…Reports of such reactions in high-pressure chemical ionization sources in analytical studies have appeared in the literature (1). The energetics of sample ion formation in chemical ionization sources have also been investigated by using these reactions (2)(3)(4). The deliberate use of charge exchange reactions in analytical mass spectrometry to study compounds of environmental interest has been reported by Hites and co-workers (5).…”
mentioning
confidence: 99%